(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Certain chemicals in cleaning products have been linked to reduced fertility, birth defects, increased risk of breast cancer, asthma, and hormone disruption. This article discusses the prevention of poisoning with toxic infections.